Regioselective, one-pot, multi-component, green synthesis of substituted benzo[c]pyrazolo[2, 7]naphthyridines. Issue 10 (5th February 2020) - Ashraf, Abida; Shafiq, Zahid; Mahmood, Khalid; Yaqub, Muhammad; Rauf, Waqar
Abstract : An efficient and environmentally benign synthetic protocol has been developed for the synthesis of benzo[ c ]pyrazolo[2, 7]naphthyridine derivatives through regioselective multi-component "on-water" reaction of isatin, malononitrile and 3-aminopyrazole. Abstract : An efficient and environmentally benign synthetic protocol has been developed for the synthesis of benzo[ c ]pyrazolo[2, 7]naphthyridine derivatives through regioselective multi-component "on-water" reaction of isatin, malononitrile and 3-aminopyrazole. The Knoevenagel condensation of isatin with malononitrile resulted in the formation of arylidene, which subsequently underwent Michael addition with 3-aminopyrazole followed by basic hydrolysis, cyclization, decarboxylation and aromatization to give the target naphthyridines in good to excellent yields. The one-pot multi-component protocol was also employed to obtain the said naphthyridines in a lower yield (10–15%) than obtained by basic hydrolysis of spiro-intermediates. The present study shows attractive features such as the use of water as a green solvent, short reaction time, reduced waste products and transition metal free C – C and C – N bond formation. The structures of the synthesized derivatives were established through FTIR, 1 H-NMR, 13 C-NMR spectroscopy and ESI-mass spectrometry.